PROFESSIONAL ACTIVITY OF THE HEAD OF A PRESCHOOL EDUCATION INSTITUTION UNDER THE CONDITIONS OF DIGITAL TRANSFORMATION OF THE EDUCATIONAL ENVIRONMENT - Orlova, Olga; Larysa, Familiarska (Professional Pedagogics, 2025)
Relevance. digital technologies and artificial intelligence are transforming society, imposing new demands on the educational paradigm, especially in managerial activities; this actualizes the need to develop relevant competencies among heads of educational institutions; the integration of artificial intelligence into the management of an educational institution optimizes processes and ensures competitiveness in line with modern challenges; in preschool education, the potential of generative artificial intelligence requires managers to be flexible and adaptive in solving professional tasks. Objective: systematization of approaches to updating the professional activities of the head of a preschool education institution using the capabilities of artificial intelligence. Methods: theoretical analysis of the regulatory and legal framework, scientific literature, and digital resources – to clarify the state of the researched problem, identify the transformation of managerial activities under the conditions of artificial intelligence integration into education; analysis, synthesis, comparison, and generalization – to systematize the features of implementing artificial intelligence technologies into the practice of the head of a preschool education institution; survey – to assess the level of adaptability and digital competence of heads of preschool education institutions in the Zhytomyr region; graphical representations – for visual illustration, interpretation, and comparison of the survey results. Results: a survey of heads of preschool education institutions was conducted to identify their attitudes towards artificial intelligence; the levels of professional competence and directions for developing targeted professional development programs were determined. Conclusions: the implementation of artificial intelligence technologies in preschool education optimizes organizational and pedagogical processes, automates routine administrative tasks, reduces the specialist's workload, and increases the efficiency of managerial activities; the integration of artificial intelligence includes using the ChatGPT model for developing instructions and schedules and Google's NotebookLM as an effective tool for working with documents; the work of the head of a preschool education institution requires updating managerial tasks (strategic planning of digital education, monitoring partnership interaction data, organizing training and data protection); adaptive competence is key to coordinating processes using digital tools and artificial intelligence, ensuring a balance between traditional values and modern technologies.
Keywords: artificial intelligence, digital technologies, managerial activity, preschool education, innovative processes